NonHodgkin's Lymphoma with Peritoneal Localization - E. Curakova; M. Genadieva-Dimitrova; J. Misevski; V. Caloska-Ivanova; V. Andreevski; B. Todorovska; U. Isahi; M. Trajkovska; P. Misevska; N. Joksimovic; S. Genadieva-Stavric; S. Antovic; et al. (Case Reports in Gastrointestinal Medicine)
The gastrointestinal tract is the most common extranodal site involved with lymphoma accounting for 5–20% of all cases. Lymphoma can occur at any site of the body, but diffuse and extensive involvement of the peritoneal cavity is unusual and rare. We report a case of diffuse large B-cell lymphoma in a 57-year-old female infiltrating the peritoneum and omentum and presenting with ascites and pleural effusion. The performed examinations did not discover any pathological findings affecting the digestive tract or parenchymal organs, except for diffuse thickening of the peritoneum and omentum. Peripheral, mediastinal, or retroperitoneal lymphadenopathy was not registered. The blood count revealed only elevated leukocytes and on examination there were no immature blood cells in the peripheral blood. The cytology from the ascites and pleural effusion did not detect any malignant cells. Due to the rapid disease progression the patient died after twenty-two days of admission. The diagnosis was discovered postmortem with the histological examination and immunohistochemical study of the material taken during the surgical laparoscopy performed four days before the lethal outcome. Although cytology is diagnostic in most cases, laparoscopy with peritoneal biopsy is the only procedure which can establish the definitive diagnosis of peritoneal lymphomatosis.